Espacio y memoria Barcelona en la novela catalana contemporánea - Łuczak, Barbara (Wydawnictwo Naukowe UAM., 2011)
Książka omawia zagadnienia przedstawienia przestrzeni Barcelony we współczesnej powieści katalońskojęzycznej. Przedmiotem analizy są formy uobecniania się tej przestrzeni w wybranych utworach oraz funkcje, jakie pełni ona w procesie konstytuowania się struktury sensów w tekście. Analizie poddano powieści uznanych twórców współczesnej literatury katalońskojęzycznej, opublikowane w drugiej połowie XX wieku i w pierwszej dekadzie wieku XXI.

The aim of the book is to study the representation of the space of Barcelona in contempo-raiy novels written in the Catalan language. It examines both the ways in which the space manifests itself in the works selected for analysis and its functions in the process of generating the structure of senses in the text. The author studies novels by well-known writers of contemporary Catalan-language literaturę published in the second half of the 20"1 century and at the beginning of the 21" century. The list includes works by Merce Rodoreda, Blai Bonet, Terenci Moix, Carme Riera and Maria Barbal.